Fisetin-metformin co-loaded in mesoporous silica nanoparticles (MSNs) inhibited triple negative breast cancer proliferation - Mohammad Reza Karimzadeh; Mahshid Samie Ghahfarokhi; Razieh Heidari; Somayeh Reiisi (Nanomedicine Journal, 2023)
Objective(s): Herbal compounds with cytotoxicity have been of great interest in recent years to improve cancer treatment methods. Fisetin is an anti-cancer herbal compound with low solubility in aqueous systems. Metformin is another compound with anti-cancer effects. In this study, the combined effect of fisetin and metformin was investigated using mesoporous silica nanoparticles (MSNs) in breast cancer cell lines. Materials and Methods: After the synthesis of nanoparticles, they were characterized using XRD, TEM, SEM. The DLS test showed a size of 143.4 nm with zeta-potential -39.1 mV. Fisetin and metformin were loaded into nanoparticles and loading was confirmed by FTIR. The toxicity of different concentrations of free drug (metformin, fisetin, fisetin-metformin) and Nanoformulations (metformin, fisetin and nano-fisetin-metformin) was investigated on two breast cancer lines MCF7 and MDA-MB-231. Results: Fisetin-metformin co-loaded in MSNs showed the highest cytotoxicity among all formulations in both cell lines. The inhibition of colony formation and migration rate was effectively observed in the co-treatment of cells with fisetin and metformin loaded in nanoparticles compared to single treatments. The expression of tumor suppressor miR-200b-3p and miR-34a-5p showed that fisetin increased the expression of these tumor suppressors compared to the control. Conclusion: The anti-cancer effect of fisetin-metformin in combination increased the expression of tumor suppressors due to the regulation of a wide range of gene network involving in cancer progress. The obtained results highlight the use of MSN as an effective drug delivery system for simultaneous delivery of herbal cytotoxic compounds in cancer.